A dual fluorescence reporter system for high throughput screening of effectors of Kiss1 gene expression - Xiaoning Li; Sijia Wang; Yanhua Lu; Huanhuan Yin; Junhua Xiao; Kai Li; Lei Ma; Yuxun Zhou (FEBS Open Bio, 2018)
Kisspeptin is a multifunctional peptide encoded by the Kiss1 gene that plays critical roles in mammalian puberty onset modulation and fertility maintenance in the hypothalamus. Understanding how Kiss1 expression is regulated is essential for elucidating the molecular mechanisms responsible for these reproductive events. In this study, we constructed an in vitro dual fluorescence reporter system to facilitate high throughput screening of effectors influencing the expression of Kiss1. In GT1‐7 cells, an enhanced GFP gene was placed under the control of the Kiss1 gene regulatory elements and translated together with this gene. A tdTomato gene cassette was simultaneously introduced into the same cell for normalization of the fluorescence signal. After treatment with different effectors, the cells were analyzed by flow cytometry. We first tested the efficacy of the system using canonical regulators and then carried out high throughput functional screening to identify chemical compounds that can regulate Kiss1 gene expression. Of 22 tested compounds from natural sources, 13 significantly affected Kiss1 expression. Verification by western blot and quantitative reverse transcription PCR (qRT‐PCR) assays and structural analysis identified two chalcone compounds as possible regulators of Kiss1 gene expression. This system may be suitable for gene functional analysis, drug screening and pharmaceutical studies.